Factors Influencing Attitude towards Islamic Finance Products among Working Adults in Malaysia - Kumaran, Karmaygan (2024)
The main issue is the lack of awareness and comprehension of the Islamic finance industry which has become a serious challenge for clients, investors, and other players in the Malaysian Islamic finance industry. Despite the government's support for Malaysian Islamic banking, some obstacles like lack of human resources, misconceptions about Islamic money, and difficulty with standardization and harmonization persist. Islamic banks, Islamic capital markets, and takaful institutions are three of the most important elements of Malaysia's Islamic financial system. A research instrument adapted from previous studies is administered for data collection on a sample of 253 respondents which consist of 150 male and 67 female. The purpose of the current research is to examine the factors that influence attitudes toward the adoption of Islamic finance. The study extends the theory of reasoned action (TRA) by incorporating additional variables such as awareness, religious obligation, and social influence. The data collected are subjected to data cleaning through SPSS 25 version and structural equation modelling using PLS-SEM 4.0. The results of the study reveal that consumer attitude towards Islamic financing is collectively determined by awareness, religious obligation, and social influence. It reflects that all three predictors (awareness, religious obligation, and social influence) are the major predictors of a consumer’s attitude toward Islamic finance at (1% p >0.000). The study also recorded an R² of 86% representing overall variance in attitude towards Islamic fiancé may be explained by the study model. In conclusion, the success of Islamic finance ultimately depends on consumer awareness, religious obligation, and social influence. The results provide vital inputs to policymakers and practitioners in offering and promoting Islamic financing. Also, the knowledge and understanding of key consumer-specific factors can be used by Islamic finance institutions in framing strategies for positioning and targeting Islamic financing products. The study is subjected to certain limitations which include the fact that the study design is cross-sectional in nature and limited to adult workers in Malaysia. Essentially, this study is a pioneering effort to apply an integrated TRA model to determine consumer attitudes to the use of Islamic financial products among adult workers in Malaysia.